A patient with a germline SDHB mutation presenting with an isolated pituitary macroprolactinoma. (21st July 2018) - Maher, Michelle; Roncaroli, Federico; Mendoza, Nigel; Meeran, Karim; Canham, Natalie; Kosicka-Slawinska, Monika; Bernhard, Birgitta; Collier, David; Drummond, Juliana; Skordilis, Kassiani; Tufton, Nicola; Gontsarova, Anastasia; et al.
Summary: Symptomatic pituitary adenomas occur with a prevalence of approximately 0.1% in the general population. It is estimated that 5% of pituitary adenomas occur in a familial setting, either in isolated or syndromic form. Recently, loss-of-function mutations in genes encoding succinate dehydrogenase subunits ( SDHx ) or MYC-associated factor X ( MAX) have been found to predispose to pituitary adenomas in co-existence with paragangliomas or phaeochromocytomas. It is rare, however, for a familial SDHx mutation to manifest as an isolated pituitary adenoma. We present the case of a pituitary lactotroph adenoma in a patient with a heterozygous germline SDHB mutation, in the absence of concomitant neoplasms. Initially, the adenoma showed biochemical response but poor tumour shrinkage in response to cabergoline; therefore, transsphenoidal surgery was performed. Following initial clinical improvement, tumour recurrence was identified 15 months later. Interestingly, re-initiation of cabergoline proved successful and the lesion demonstrated both biochemical response and tumour shrinkage. Our patient's SDHB mutation was identified when we realised that her father had a metastatic paraganglioma, prompting genetic testing. Re-inspection of the histopathological report of the prolactinoma confirmed cells with vacuolated cytoplasm. This histological feature is suggestive of an SDHx mutation and should prompt further screening for mutations by immunohistochemistry and/or genetic testing. Surprisingly, immunohistochemistry of this pituitary adenoma demonstrated normal SDHB expression, despite loss of SDHB expression in the patient's father's paraganglioma. Learning points: Pituitary adenomas may be the presenting and/or sole feature of SDHB mutation-related disease. SDHx mutated pituitary adenomas may display clinically aggressive behaviour and demonstrate variable response to medical treatment. Histological evidence of intracytoplasmic vacuoles in a pituitary adenoma might suggest an SDH-deficient tumour and should prompt further screening for SDHx mutations. Immunohistochemistry may not always predict the presence of SDHx mutations.